PELATIHAN PENERAPAN APLIKASI CLASSPOINT UNTUK GURU SEBAGAI MEDIA PEMBELAJARAN PEMBUATAN KUIS INTERAKTIF DI KELAS - Meilisa, Ranny; Oktadela, Resy (Batara Wisnu : Indonesian Journal of Community Services, 2025)
Facing the big challenges in the era of the industrial revolution 4.0, education is required to adapt, including education at the elementary and secondary levels. The educational challenges of the 4.0 revolution, especially in Indonesia, one of which is the massive media that is in accordance with the demands of the times. For this reason, educators must master technology in order to adapt to students. Presentations using PowerPoint are commonly used, especially by teachers. This service seeks to optimize learning with applications that can be integrated with the use of PowerPoint, the application is called classpoint. Training on the use of classpoint as an interactive learning media for teachers aims to improve the teaching and learning skills of teachers in integrating modern technology into the classroom. The results of this training can provide new insights for MTs Al-Muttaqin teachers in utilizing educational technology to create a more dynamic and interesting learning environment for students.